Analysis of transcriptomic alterations induced by 33 different per- and polyfluoroalkyl substances (PFAS) in differentiated HepaRG cells - Heike Sprenger; Wiebke Alker; Anna Rocchi; Chiara Leo; Rosa Giglio; Greta Immobile Molaro; Francesco Dondero; Albert Braeuning; Thorsten Buhrke (Archives of Toxicology, 2026)
Due to their high persistence and adverse health effects in humans the use of a number of per- and polyfluoroalkyl substances (PFAS) has been restricted. As a consequence, novel PFAS are increasingly being introduced for industrial applications, although toxicological data are still limited or lacking for many of these compounds. This study examined the molecular mechanisms of action of novel PFAS with a focus on mono- and polyether PFAS with linear or branched structures and either carboxylic acid or sulfonic acid functional groups. Differentiated HepaRG cells, a model of human hepatocytes, were exposed for 24 h to different PFAS congeners at three non-cytotoxic concentrations each. Total RNA was isolated and subjected to whole transcriptome analysis. The study provides transcriptomic data for in total 33 PFAS congeners, for 13 of them for the first time. For most PFAS, the number of differentially expressed genes (DEG) increased in a concentration-dependent manner, whereas five PFAS induced only minor transcriptional changes even at the highest test concentration. Ingenuity Pathway Analysis (IPA) revealed broadly comparable transcriptional responses across all 33 PFAS, indicating convergent molecular effects in HepaRG cells despite marked structural differences among the PFAS congeners. The tested PFAS consistently activated canonical pathways related to fatty acid and lipid metabolism, mainly regulated by the nuclear receptor PPARα, and also affected pathways related to xenobiotic metabolism, partially linked to PXR and CAR signaling. In addition, several PFAS inhibited cholesterol and bile acid biosynthesis pathways. IPA further predicted effects on hepatocyte-relevant upstream regulators such as HNF4A, HNF1A, and FOXA2. Finally, IPA tox-function analysis indicated associations between PFAS-induced transcriptional changes and liver diseases related to cholestasis.

Pregnane X receptor-mediated liver growth: a controlled clinical trial in healthy volunteers and identification of the role of AKT–MTOR pathway in mouse - Piia Lassila; Mikko Karpale; Outi Kummu; Aaron Stahl; Aki Käräjämäki; Eija Pääkkö; Helen Sophie Hammer; Albert Braeuning; Oliver Pötz; Markus Templin; Janne Hukkanen; Jukka Hakkola (Archives of Toxicology, 2026)
Pregnane X receptor (PXR) is a nuclear receptor acting as a master xenobiotic receptor for many exogenous chemicals. Activation of PXR has been linked to liver growth in mice, usually via interaction with Yes-associated protein (YAP), but this adaptive response has not been observed in humans. We investigated the effect of human PXR agonist, rifampicin, on liver size in a controlled clinical trial in healthy volunteers. Moreover, we developed a novel protocol to reveal mechanisms of PXR-mediated liver growth in mice. One-week rifampicin treatment caused a 2.7% mean increase in liver volume-to-body weight ratio without affecting liver fat content in human volunteers (n=16). Pxr −/− mice were transduced with adenovirus carrying either murine PXR or green fluorescent protein and both groups were treated with pregnenolone−16α-carbonitrile (PCN) for 0 to 4 days. In this setup, activation of PXR with PCN significantly increased liver size in male mice already after 1-day PCN treatment and the liver growth was further enhanced after 4 days. No significant liver enlargement was observed in female mice. 4-day PCN treatment also improved glucose tolerance in the male mice. RNA-sequencing revealed upregulation of genes and pathways involved in proliferation. DigiWest protein profiling and immunoblotting revealed increased activity of AKT–mammalian target of rapamycin (MTOR) pathway in the male mice. In contrast, we did not observe YAP activation. Our results indicate that PXR activation induces liver growth and activates proliferative AKT–MTOR pathway in male mice and may also induce liver growth in humans.

Cell line identity rather than medium composition determines transcriptomic profiles of HepaRG and HuH7 cells cultured in chemically defined or serum-based media: comparison with primary human hepatocytes - Ahmed S. M. Ali; Heike Sprenger; Albert Braeuning; Jens Kurreck (Archives of Toxicology, 2026)
Standardized and reproducible cell models are key to replace animal testing in toxicology. The composition of culture medium is a major, yet frequently undercontrolled, determinant of cell state in vitro. For decades, fetal bovine serum (FBS) has been routinely incorporated into liver cell culture. Its undefined and lot-to-lot variable composition can, however, confound cell identity and experimental reproducibility. Chemically defined media (CDM) represent an alternative approach that can improve standardization, but the consequences of transitioning from FBS-supplemented media (FBS-SM) to CDM remain insufficiently characterized in hepatic models, particularly with respect to metabolic and detoxification programs that govern xenobiotic metabolism and hepatotoxicity readouts. Here, we systematically assessed how replacing FBS-SM with CDM remodels transcriptomic profiles in two widely used human hepatic cell lines (HepaRG and HuH7 cells) and compared the results to that obtained from primary human hepatocytes (PHH). Global transcriptomic analyses indicated that cell type was the primary driver of variance, whereas medium induced a model-dependent secondary effect. Functional interpretation showed preferential enhancement of xenobiotic metabolism and transport-associated programs in HepaRG cells, while HuH7 cells response was dominated by lipid/sterol homeostasis and stress-linked processes. Benchmarking against PHH based on hepatic identity and detoxification gene panels further supported improved PHH alignment for HepaRG cells under CDM compared to cultures with FBS-SM, with limited improvement for HuH7 cells. Collectively, these findings show that medium effects must be interpreted in the context of cell line identity and indicate that HepaRG cells cultured in CDM provide a more PHH-like transcriptomic background for in vitro studies of xenobiotic metabolism and hepatotoxicity-related readouts than HuH7 cells.

Development of a QSAR model for predicting PPARα activation by PFAS based on human in vitro data of a comprehensive panel of legacy and novel PFAS - Wiebke Alker; Periklis Tsiros; Haralambos Sarimveis; Albert Braeuning; Thorsten Buhrke (Archives of Toxicology, 2026)
Per- and polyfluoroalkyl substances (PFAS) are a large family of persistent environmental contaminants. Some PFAS are known to bioaccumulate, are frequently detected in human serum, and are associated with several adverse effects on the immune system, the endocrine system, and the liver. PFAS-mediated activation of the peroxisome proliferator-activated receptor alpha (PPARα), which plays a key role in lipid and cholesterol homeostasis, is suggested to be an important molecular initiating event triggering PFAS toxicity. The aim of this study was to evaluate the PPARα activation potential of a diverse panel of 34 PFAS congeners, consisting of both legacy and novel compounds, using a PPARα-dependent transactivation assay in transfected HEK293T cells. The resulting concentration-response data were analyzed using benchmark dose (BMD) modelling to quantify PPARα activation potency. A key finding was that PFAS with a sulfonic acid group showed a lower potency compared to those with a carboxylic group. The most potent activators belonged to the perfluoroalkylether carboxylic acid (PFECA) subgroup. Computational descriptors were generated to characterize each congener, and quantitative structure-activity relationship (QSAR) modelling was applied to relate molecular features to in vitro PPARα activation potency, as expressed by BMD estimates. For prioritization purposes in the context of PFAS hazard characterization, the QSAR model was used to screen about 10,000 PFAS congeners. Of these, roughly 10% were within the defined applicability domain of the developed QSAR model. Predicted BMD concentrations for PPARα activation were in the range between 0.3 µM and 420 µM.

Cytochrome P450 enzymes as modulators of oncogenic signaling via the Wnt/β-catenin signaling pathway - Albert Braeuning (Archives of Toxicology, 2026)
Enzymes from the cytochrome P450 (CYP) superfamily, especially from families CYP1, CYP2, and CYP3, play a decisive role in phase I of drug and xenobiotic metabolism in mammalian organisms. The enzymes are responsible for metabolic conversion and detoxification of a plethora of foreign molecules. Metabolic conversion of pro-carcinogenic compounds links CYP enzyme activities to cancer development, while in addition oncogenic pathways have been shown to regulate the expression of CYP genes, together with the well-known regulation by nuclear receptors acting as ligand-activated transcription factors triggered by exposure to xenobiotics. Specifically, the Wnt/β-catenin signaling pathway is among the recently established transcriptional regulators of CYP enzymes. β-Catenin is well-known as a key player in organism development and, when aberrantly activated, a major oncogenic driver of carcinogenesis. While the latter phenomena are rather well-described, new evidence suggests that CYP enzymes themselves may, under certain conditions, also affect the activity of the β-catenin pathway and thereby could impact on carcinogenesis in a way different from toxifying or detoxifying foreign compounds. This review focuses on the currently available knowledge about the regulation of β-catenin-dependent signaling by CYP enzymes. The synopsis of data reveals the possibility of a previously undervalued role of CYPs in the regulation of Wnt/β-catenin signaling, and possible molecular mechanisms are highlighted.

New approach methodologies for metabolic disruption: a high-throughput human liver cell phospholipidosis assay - Neele Wewer; Albert Braeuning; Dajana Lichtenstein (Archives of Toxicology, 2026)
Phospholipidosis (PLD) is the excessive accumulation of phospholipids within cells, which is, for example, observed in the liver following exposure to certain chemicals or drugs. Although the precise molecular mechanisms underlying PLD remain incompletely elucidated, it is documented that PLD is frequently induced by cationic amphiphilic compounds. To facilitate the identification of potential PLD inducers across diverse groups of chemicals, the development of novel high-throughput screening methodologies is imperative. Here, an in vitro human liver cell culture system was established for PLD screening, employing the fluorescence-based LipidTox assay in differentiated HepaRG cells in a 96-well format. Cells were treated with a selection of 35 compounds characterized as either PLD inducers or non-inducers, based on previously published in vivo data. Concentration-response curves of phospholipid accumulation were assessed and the results were compared with existing in vivo, in vitro and in silico datasets. The findings confirm the applicability of the LipidTOX assay in differentiated HepaRG cells as a reliable in vitro -based high-throughput screening method for PLD prediction, achieving an overall predictivity of 86%.

Proteomic insights into novel food insects: Homology-based proteome characterization and allergenicity considerations for EU-regulated insect species - Tobias Meisinger; Hannes Planatscher; Albert Braeuning; Eva-Maria Ladenburger; Dieter Stoll; Cristiano Garino; Hermann Broll; Oliver Poetz (Food Control, 2025)

NAM-based analysis of contaminant short-term organ toxicity in HepaRG and RPTEC/TERT1 cells - Kristina Jochum; Andrea Miccoli; Cornelia Sommersdorf; Oliver Poetz; Albert Braeuning; Tewes Tralau; Philip Marx-Stoelting (Toxicology, 2025)

A group of novel polyfluoroether substances affects lipid metabolism in human hepatocyte HepaRG cells less than classic perfluoroalkyl compounds - Faezeh Sadrabadi; Wiebke Alker; Heike Sprenger; Albert Braeuning; Thorsten Buhrke (Toxicology in Vitro, 2025)

Hazard characterization of the mycotoxins enniatins and beauvericin to identify data gaps and improve risk assessment for human health - Anne-Cathrin Behr; Christiane Kruse Fæste; Amaya Azqueta; Ana M. Tavares; Anastasia Spyropoulou; Anita Solhaug; Ann-Karin Olsen; Ariane Vettorazzi; Birgit Mertens; Bojana Zegura; Camille Streel; Dieynaba Ndiaye; et al. (Archives of Toxicology, 2025)
Enniatins (ENNs) and beauvericin (BEA) are cyclic hexadepsipeptide fungal metabolites which have demonstrated antibiotic, antimycotic, and insecticidal activities. The substantial toxic potentials of these mycotoxins are associated with their ionophoric molecular properties and relatively high lipophilicities. ENNs occur extensively in grain and grain-derived products and are considered a food safety issue by the European Food Safety Authority (EFSA). The tolerable daily intake and maximum levels for ENNs in humans and animals remain unestablished due to key toxicological and toxicokinetic data gaps, preventing full risk assessment. Aiming to find critical data gaps impeding hazard characterization and risk evaluation, this review presents a comprehensive summary of the existing information from in vitro and in vivo studies on toxicokinetic characteristics and cytotoxic, genotoxic, immunotoxic, endocrine, reproductive and developmental effects of the most prevalent ENN analogues (ENN A, A1, B, B1) and BEA. The missing information identified showed that additional studies on ENNs and BEA have to be performed before sufficient data for an in-depth hazard characterisation of these mycotoxins become available.

Current status and trends in the analysis of GMO and new genomic techniques - Hermann Broll; Joachim Bendiek; Albert Braeuning; Kolja Neil Eckermann; Anuscha Gebhardt; Lutz Grohmann; Nina Keiss; Jörn Lämke; Joachim Mankertz; Werner Schenkel; Ursula Vincent; Christopher Weidner; et al. (Journal of Consumer Protection and Food Safety, 2025)
The detection of genetically modified organisms (GMO) is crucial for regulatory compliance and market control. Therefore, detection methods are constantly being developed and improved. New genomic techniques (NGT) present unique challenges for detection due to the minimal genetic changes they introduce. The ‘International Conference on GMO Analysis and New Genomic Techniques’ held in March 2023 in Berlin, explored advances in detection methods, such as Next-Generation Sequencing and digital PCR, and highlighted the need for global cooperation and capacity-building initiatives. The conference emphasized international collaboration and addressed the challenges of establishing robust methods for identifying NGT-derived organisms.

An integrated multi-omics analysis of the effects of the food processing-induced contaminant 2-monochloropropane-1,3-diol (2-MCPD) in rat heart - Lucien G. J. Cayer; Thorsten Buhrke; Jennifer Roberts; Andrée Nunnikhoven; Katharina Sommerkorn; Anna Reinhold; Albert Braeuning; Jayadev Raju; Harold M. Aukema; Tobias Karakach (Archives of Toxicology, 2024)
Many foods including edible oils contain 2-monochloropropane-1,3-diol (2-MCPD), a processing-induced chemical contaminant. Cardiotoxic effects have been shown to result from oral 2-MCPD exposure in rodents, but the underlying mechanisms of action remain poorly understood. We undertook a comprehensive multi-omics approach to assess changes at the transcriptomic, proteomic, and oxylipin levels in heart tissues from male F344 rats that were exposed to 0 or 40 mg/kg BW/day of 2-MCPD in the diet for 90 days, in a regulatory compliant rodent bioassay. Heart tissues were collected for RNA sequencing, quantitative PCR analysis, proteomic analysis via two-dimensional gel electrophoresis and mass spectrometry, and targeted lipidomic profiling by high-performance liquid chromatography–tandem mass spectrometry (HPLC–MS/MS). Transcriptomic and proteomic data analyses revealed upregulation of immune/inflammatory response processes and downregulation of energy metabolism and cardiac structure and functions. Among differentially expressed gene–protein pairs, coronin-1A, a key leukocyte-regulating protein, emerged as markedly up-regulated. Oxylipin profiling highlighted a selective suppression of docosahexaenoic acid-derived metabolites, suggesting a disruption in cardioprotective lipid pathways. These findings suggest that 2-MCPD disrupts homeostasis through inflammatory activation and suppression of metabolic and cardiac function. This research provides insights into 2-MCPD's cardiotoxicity, emphasizing the need for further studies to support hazard characterization.

The zebrafish embryo as a model for chemically-induced steatosis: A case study with three pesticides - Harm J. Heusinkveld; Edwin P. Zwart; Angela de Haan; Albert Braeuning; Jimmy Alarcan; Leo T.M. van der Ven (Toxicology, 2024)

Comparative case study on NAMs: towards enhancing specific target organ toxicity analysis - Kristina Jochum; Andrea Miccoli; Cornelia Sommersdorf; Oliver Poetz; Albert Braeuning; Tewes Tralau; Philip Marx-Stoelting (Archives of Toxicology, 2024)
Traditional risk assessment methodologies in toxicology have relied upon animal testing, despite concerns regarding interspecies consistency, reproducibility, costs, and ethics. New Approach Methodologies (NAMs), including cell culture and multi-level omics analyses, hold promise by providing mechanistic information rather than assessing organ pathology. However, NAMs face limitations, like lacking a whole organism and restricted toxicokinetic interactions. This is an inherent challenge when it comes to the use of omics data from in vitro studies for the prediction of organ toxicity in vivo. One solution in this context are comparative in vitro–in vivo studies as they allow for a more detailed assessment of the transferability of the respective NAM data. Hence, hepatotoxic and nephrotoxic pesticide active substances were tested in human cell lines and the results subsequently related to the biology underlying established effects in vivo. To this end, substances were tested in HepaRG and RPTEC/tERT1 cells at non-cytotoxic concentrations and analyzed for effects on the transcriptome and parts of the proteome using quantitative real-time PCR arrays and multiplexed microsphere-based sandwich immunoassays, respectively. Transcriptomics data were analyzed using three bioinformatics tools. Where possible, in vitro endpoints were connected to in vivo observations. Targeted protein analysis revealed various affected pathways, with generally fewer effects present in RPTEC/tERT1. The strongest transcriptional impact was observed for Chlorotoluron in HepaRG cells (increased CYP1A1 and CYP1A2 expression). A comprehensive comparison of early cellular responses with data from in vivo studies revealed that transcriptomics outperformed targeted protein analysis, correctly predicting up to 50% of in vivo effects.

In vitro screening of understudied PFAS with a focus on lipid metabolism disruption - Lackson Kashobwe; Faezeh Sadrabadi; Albert Braeuning; Pim E. G. Leonards; Thorsten Buhrke; Timo Hamers (Archives of Toxicology, 2024)
Per- and polyfluoroalkyl substances (PFAS) are man-made chemicals used in many industrial applications. Exposure to PFAS is associated with several health risks, including a decrease in infant birth weight, hepatoxicity, disruption of lipid metabolism, and decreased immune response. We used the in vitro cell models to screen six less studied PFAS [perfluorooctane sulfonamide (PFOSA), perfluoropentanoic acid (PFPeA), perfluoropropionic acid (PFPrA), 6:2 fluorotelomer alcohol (6:2 FTOH), 6:2 fluorotelomer sulfonic acid (6:2 FTSA), and 8:2 fluorotelomer sulfonic acid (8:2 FTSA)] for their capacity to activate nuclear receptors and to cause differential expression of genes involved in lipid metabolism. Cytotoxicity assays were run in parallel to exclude that observed differential gene expression was due to cytotoxicity. Based on the cytotoxicity assays and gene expression studies, PFOSA was shown to be more potent than other tested PFAS. PFOSA decreased the gene expression of crucial genes involved in bile acid synthesis and detoxification, cholesterol synthesis, bile acid and cholesterol transport, and lipid metabolism regulation. Except for 6:2 FTOH and 8:2 FTSA, all tested PFAS downregulated PPARA gene expression. The reporter gene assay also showed that 8:2 FTSA transactivated the farnesoid X receptor (FXR). Based on this study, PFOSA, 6:2 FTSA, and 8:2 FTSA were prioritized for further studies to confirm and understand their possible effects on hepatic lipid metabolism.

A multi-omics approach to elucidate okadaic acid-induced changes in human HepaRG hepatocarcinoma cells - Leonie T. D. Wuerger; Heike Sprenger; Ksenia Krasikova; Markus Templin; Aaron Stahl; Uta M. Herfurth; Holger Sieg; Albert Braeuning (Archives of Toxicology, 2024)
Okadaic acid (OA), a prevalent marine biotoxin found in shellfish, is known for causing acute gastrointestinal symptoms. Despite its potential to reach the bloodstream and the liver, the hepatic effects of OA are not well understood, highlighting a significant research gap. This study aims to comprehensively elucidate the impact of OA on the liver by examining the transcriptome, proteome, and phosphoproteome alterations in human HepaRG liver cells exposed to non-cytotoxic OA concentrations. We employed an integrative multi-omics approach, encompassing RNA sequencing, shotgun proteomics, phosphoproteomics, and targeted DigiWest analysis. This enabled a detailed exploration of gene and protein expression changes, alongside phosphorylation patterns under OA treatment. The study reveals concentration- and time-dependent deregulation in gene and protein expression, with a significant down-regulation of xenobiotic and lipid metabolism pathways. Up-regulated pathways include actin crosslink formation and a deregulation of apoptotic pathways. Notably, our results revealed that OA, as a potent phosphatase inhibitor, induces alterations in actin filament organization. Phosphoproteomics data highlighted the importance of phosphorylation in enzyme activity regulation, particularly affecting proteins involved in the regulation of the cytoskeleton. OA's inhibition of PP2A further leads to various downstream effects, including alterations in protein translation and energy metabolism. This research expands the understanding of OA's systemic impact, emphasizing its role in modulating the phosphorylation landscape, which influences crucial cellular processes. The results underscore OA's multifaceted effects on the liver, particularly through PP2A inhibition, impacting xenobiotic metabolism, cytoskeletal dynamics, and energy homeostasis. These insights enhance our comprehension of OA's biological significance and potential health risks.

Legacy and alternative per- and polyfluoroalkyl substances (PFAS) alter the lipid profile of HepaRG cells - Lackson Kashobwe; Faezeh Sadrabadi; Lars Brunken; Ana Carolina M.F. Coelho; Torkjel M. Sandanger; Albert Braeuning; Thorsten Buhrke; Mattias Öberg; Timo Hamers; Pim.E.G. Leonards (Toxicology, 2024)

Effects of marine biotoxins on drug-metabolizing cytochrome P450 enzymes and their regulation in mammalian cells - Leonie T. D. Würger; Jimmy Alarcan; Albert Braeuning (Archives of Toxicology, 2024)
Marine biotoxins are a heterogenous group of natural toxins, which are able to trigger different types of toxicological responses in animals and humans. Health effects arising from exposure to marine biotoxins are ranging, for example, from gastrointestinal symptoms to neurological effects, depending on the individual toxin(s) ingested. Recent research has shown that the marine biotoxin okadaic acid (OA) can strongly diminish the expression of drug-metabolizing cytochrome P450 (CYP) enzymes in human liver cells by a mechanism involving proinflammatory signaling. By doing so, OA may interfere with the metabolic barrier function of liver and intestine, and thus alter the toxico- or pharmacokinetic properties of other compounds. Such effects of marine biotoxins on drug and xenobiotic metabolism have, however, not been much in the focus of research yet. In this review, we present the current knowledge on the effects of marine biotoxins on CYP enzymes in mammalian cells. In addition, the role of CYP-regulating nuclear receptors as well as inflammatory signaling in the regulation of CYPs by marine biotoxins is discussed. Strong evidence is available for effects of OA on CYP enzymes, along with information about possible molecular mechanisms. For other marine biotoxins, knowledge on effects on drug metabolism, however, is scarce.

Particulate iron oxide food colorants (E 172) during artificial digestion and their uptake and impact on intestinal cells - Holger Sieg; Caroline Schaar; Nicole Fouquet; Linda Böhmert; Andreas F. Thünemann; Albert Braeuning (Toxicology in Vitro, 2024)

Influence of artificial digestion on characteristics and intestinal cellular effects of micro-, submicro- and nanoplastics - Maxi B. Paul; Linda Böhmert; Andreas F. Thünemann; Katrin Loeschner; Lucas Givelet; Christoph Fahrenson; Albert Braeuning; Holger Sieg (Food and Chemical Toxicology, 2024)

Impact of perfluoroalkyl substances (PFAS) and PFAS mixtures on lipid metabolism in differentiated HepaRG cells as a model for human hepatocytes - Faezeh Sadrabadi; Jimmy Alarcan; Heike Sprenger; Albert Braeuning; Thorsten Buhrke (Archives of Toxicology, 2024)
Per- and polyfluoroalkyl substances (PFAS) are environmental contaminants with various adverse health effects in humans including disruption of lipid metabolism. Aim of the present study was to elucidate the molecular mechanisms of PFAS-mediated effects on lipid metabolism in human cells. Here, we examined the impact of a number of PFAS (PFOS, PFOA, PFNA, PFDA, PFHxA, PFBA, PFHxS, PFBS, HFPO-DA, and PMPP) and of some exposure-relevant PFAS mixtures being composed of PFOS, PFOA, PFNA and PFHxS on lipid metabolism in human HepaRG cells, an in vitro model for human hepatocytes. At near cytotoxic concentrations, the selected PFAS and PFAS mixtures induced triglyceride accumulation in HepaRG cells and consistently affected the expression of marker genes for steatosis, as well as PPARα target genes and genes related to lipid and cholesterol metabolism, pointing to common molecular mechanisms of PFAS in disrupting cellular lipid and cholesterol homeostasis. PPARα activation was examined by a transactivation assay in HEK293T cells, and synergistic effects were observed for the selected PFAS mixtures at sum concentrations higher than 25 µM, whereas additivity was observed at sum concentrations lower than 25 µM. Of note, any effect observed in the in vitro assays occurred at PFAS concentrations that were at least four to five magnitudes above real-life internal exposure levels of the general population.

A human Caco-2-based co-culture model of the inflamed intestinal mucosa for particle toxicity studies - Maxi B. Paul; Marén Schlief; Hannes Daher; Albert Braeuning; Holger Sieg; Linda Böhmert (In vitro models, 2023)
The intestinal barrier is a complex interface of the human body, possessing the largest contact surface to nutrients and antigens and containing a major part of the immune system. It has to deal with continuous exposure to a broad mixture of essential, harmful, or useless substances and particles. In the context of plastic pollution and the ubiquitous occurrence of micro- and nanoplastics, oral exposure to such particles is of particular interest. Standard intestinal in vitro models, however, are unable to mimic the role of the immune system in the particle-exposed intestine. To allow for a closer look on the effect of particles on the intestinal immune system, we here developed a co-culture model to enable investigation of the epithelial brush border monolayer in a healthy and inflamed state. The model is based on well-established Caco-2 intestinal epithelial cells cultured in a Transwell™ system. Intraepithelial immune cells were mimicked by THP-1-derived M0-macrophages and MUTZ-3-derived dendritic cells. To fulfill the requirements needed for the investigation of particles, the co-culture system was developed without an additional matrix layer. Cell–cell contacts were established between interstitial and immune cells, and the Caco-2 standard cell culture medium was used, which is well-characterized for its role in defining the identity of particle dispersions. The model was characterized using confocal microscopy, membrane integrity measurements, and cytokine release assays from inflamed and healthy cells. Finally, the new co-culture model was used for investigation on polylactic acid, melamine formaldehyde resin, and polymethylmethacrylate plastic micro- and nanoparticles.

3-MCPD as contaminant in processed foods: State of knowledge and remaining challenges - Andreas Eisenreich; Bernhard H. Monien; Mario E. Götz; Thorsten Buhrke; Axel Oberemm; Katharina Schultrich; Klaus Abraham; Albert Braeuning; Bernd Schäfer (Food Chemistry, 2023)

Proteomic analysis of hepatic effects of phenobarbital in mice with humanized liver - Heike Sprenger; Josef Daniel Rasinger; Helen Hammer; Wael Naboulsi; Elke Zabinsky; Hannes Planatscher; Michael Schwarz; Oliver Poetz; Albert Braeuning (Archives of Toxicology, 2022)
Activation of the constitutive androstane receptor (CAR) may induce adaptive but also adverse effects in rodent liver, including the induction of drug-metabolizing enzymes, transient hepatocellular proliferation, and promotion of liver tumor growth. Human relevance of CAR-related adverse hepatic effects is controversially debated. Here, we used the chimeric FRG-KO mouse model with livers largely repopulated by human hepatocytes, in order to study human hepatocytes and their response to treatment with the model CAR activator phenobarbital (PB) in vivo. Mice received an intraperitoneal injection with 50 mg/kg body weight PB or saline, and were sacrificed after 72–144 h. Non-repopulated FRG-KO mice were used as additional control. Comprehensive proteomics datasets were generated by merging data obtained by targeted as well as non-targeted proteomics approaches. For the first time, a novel proteomics workflow was established to comparatively analyze the effects of PB on human and murine proteins within one sample. Analysis of merged proteome data sets and bioinformatics data mining revealed comparable responses in murine and human hepatocytes with respect to nuclear receptor activation and induction of xenobiotic metabolism. By contrast, activation of MYC, a key regulator of proliferation, was predicted only for mouse but not human hepatocytes. Analyses of 5-bromo-2′-deoxyuridine incorporation confirmed this finding. In summary, this study for the first time presents a comprehensive proteomic analysis of CAR-dependent effects in human and mouse hepatocytes from humanized FRG-KO mice. The data support the hypothesis that PB does induce adaptive metabolic responses, but not hepatocellular proliferation in human hepatocytes in vivo.

An approach for mixture testing and prioritization based on common kinetic groups - Albert Braeuning; Denise Bloch; Mawien Karaca; Carsten Kneuer; Stefanie Rotter; Tewes Tralau; Philip Marx-Stoelting (Archives of Toxicology, 2022)
In light of an ever-increasing exposure to chemicals, the topic of potential mixture toxicity has gained increased attention, particularly as the toxicological toolbox to address such questions has vastly improved. Routinely toxicological risk assessments will rely on the analysis of individual compounds with mixture effects being considered only in those specific cases where co-exposure is foreseeable, for example for pesticides or food contact materials. In the field of pesticides, active substances are summarized in so-called cumulative assessment groups (CAG) which are primarily based on their toxicodynamic properties, that is, respective target organs and mode of action (MoA). In this context, compounds causing toxicity by a similar MoA are assumed to follow a model of dose/concentration addition (DACA). However, the respective approach inherently falls short of addressing cases where there are dissimilar or independent MoAs resulting in wider toxicokinetic effects. Yet, the latter are often the underlying cause when effects deviate from the DACA model. In the present manuscript, we therefore suggest additionally to consider toxicokinetic effects (especially related to xenobiotic metabolism and transporter interaction) for the grouping of substances to predict mixture toxicity. In line with the concept of MoA-based CAGs, we propose common kinetics groups (CKGs) as an additional tool for grouping of chemicals and mixture prioritization. Fundamentals of the CKG concept are discussed, along with challenges for its implementation, and methodological approaches and examples are explored.

Investigating the in vitro steatotic mixture effects of similarly and dissimilarly acting test compounds using an adverse outcome pathway-based approach - Jimmy Alarcan; Georges de Sousa; Efrosini S. Katsanou; Anastasia Spyropoulou; Petros Batakis; Kyriaki Machera; Roger Rahmani; Alfonso Lampen; Albert Braeuning; Dajana Lichtenstein (Archives of Toxicology, 2022)
Within the EuroMix project, we have previously developed an adverse outcome pathway (AOP)-based in vitro assay toolbox to investigate the combined effects of liver steatosis-inducing compounds in human HepaRG hepatocarcinoma cells. In this study, we applied the toolbox to further investigate mixture effects of combinations, featuring either similarly acting or dissimilarly acting substances. The valproic acid structural analogs 2-propylheptanoic acid (PHP) and 2-propylhexanoic acid (PHX) were chosen for establishing mixtures of similarly acting substances, while a combination with the pesticidal active substance clothianidin (CTD) was chosen for establishing mixtures of dissimilarly acting compounds. We first determined relative potency factors (RPFs) for each compound based on triglyceride accumulation results. Thereafter, equipotent mixtures were tested for nuclear receptor activation in transfected HepG2 cells, while gene expression and triglyceride accumulation were investigated in HepaRG cells, following the proposed AOP for liver steatosis. Dose addition was observed for all combinations and endpoints tested, indicating the validity of the additivity assumption also in the case of the tested mixtures of dissimilarly acting substances. Gene expression results indicate that the existing steatosis AOP can still be refined with respect to the early key event (KE) of gene expression, in order to reflect the diversity of molecular mechanisms underlying the adverse outcome.

Correction to: Impairment of bile acid metabolism by perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) in human HepaRG hepatoma cells - Anne‑Cathrin Behr; Anna Kwiatkowski; Marcus Stahlman; Felix Florian Schmidt; Claudia Luckert; Albert Braeuning; Thorsten Buhrke (Archives of Toxicology, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s00204-021-03089-x

Pyrrolizidine alkaloid-induced transcriptomic changes in rat lungs in a 28-day subacute feeding study - Julia Buchmueller; Heike Sprenger; Johanna Ebmeyer; Josef Daniel Rasinger; Otto Creutzenberg; Dirk Schaudien; Jan G. Hengstler; Georgia Guenther; Albert Braeuning; Stefanie Hessel-Pras (Archives of Toxicology, 2021)
Pyrrolizidine alkaloids (PAs) are secondary plant metabolites synthesized by a wide range of plants as protection against herbivores. These toxins are found worldwide and pose a threat to human health. PAs induce acute effects like hepatic sinusoidal obstruction syndrome and pulmonary arterial hypertension. Moreover, chronic exposure to low doses can induce cancer and liver cirrhosis in laboratory animals. The mechanisms causing hepatotoxicity have been investigated previously. However, toxic effects in the lung are less well understood, and especially data on the correlation effects with individual chemical structures of different PAs are lacking. The present study focuses on the identification of gene expression changes in vivo in rat lungs after exposure to six structurally different PAs (echimidine, heliotrine, lasiocarpine, senecionine, senkirkine, and platyphylline). Rats were treated by gavage with daily doses of 3.3 mg PA/kg bodyweight for 28 days and transcriptional changes in the lung and kidney were investigated by whole-genome microarray analysis. The results were compared with recently published data on gene regulation in the liver. Using bioinformatics data mining, we identified inflammatory responses as a predominant feature in rat lungs. By comparison, in liver, early molecular consequences to PAs were characterized by alterations in cell-cycle regulation and DNA damage response. Our results provide, for the first time, information about early molecular effects in lung tissue after subacute exposure to PAs, and demonstrates tissue-specificity of PA-induced molecular effects.

Subcellular spatio-temporal intravital kinetics of aflatoxin B1 and ochratoxin A in liver and kidney - Ahmed Ghallab; Reham Hassan; Maiju Myllys; Wiebke Albrecht; Adrian Friebel; Stefan Hoehme; Ute Hofmann; Abdel-latif Seddek; Albert Braeuning; Lars Kuepfer; Benedikt Cramer; Hans-Ulrich Humpf; et al. (Archives of Toxicology, 2021)
Local accumulation of xenobiotics in human and animal tissues may cause adverse effects. Large differences in their concentrations may exist between individual cell types, often due to the expression of specific uptake and export carriers. Here we established a two-photon microscopy-based technique for spatio-temporal detection of the distribution of mycotoxins in intact kidneys and livers of anesthetized mice with subcellular resolution. The mycotoxins ochratoxin A (OTA, 10 mg/kg b.w.) and aflatoxin B 1 (AFB 1 , 1.5 mg/kg b.w.), which both show blue auto-fluorescence, were analyzed after intravenous bolus injections. Within seconds after administration, OTA was filtered by glomeruli, and enriched in distal tubular epithelial cells (dTEC). A striking feature of AFB 1 toxicokinetics was its very rapid uptake from sinusoidal blood into hepatocytes ( t 1/2 ~ 4 min) and excretion into bile canaliculi. Interestingly, AFB 1 was enriched in the nuclei of hepatocytes with zonal differences in clearance. In the cytoplasm of pericentral hepatocytes, the half-life ( t 1/2 ~ 63 min) was much longer compared to periportal hepatocytes of the same lobules ( t 1/2 ~ 9 min). In addition, nuclear AFB 1 from periportal hepatocytes cleared faster compared to the pericentral region. These local differences in AFB 1 clearance may be due to the pericentral expression of cytochrome P450 enzymes that activate AFB 1 to protein- and DNA-binding metabolites. In conclusion, the present study shows that large spatio-temporal concentration differences exist within the same tissues and its analysis may provide valuable additional information to conventional toxicokinetic studies.

Mixture prioritization and testing: the importance of toxicokinetics - Albert Braeuning; Philip Marx-Stoelting (Archives of Toxicology, 2021)

More than additive effects on liver triglyceride accumulation by combinations of steatotic and non-steatotic pesticides in HepaRG cells - Alexandra Lasch; Philip Marx-Stoelting; Albert Braeuning; Dajana Lichtenstein (Archives of Toxicology, 2021)
The liver is constantly exposed to mixtures of hepatotoxic compounds, such as food contaminants and pesticides. Dose addition is regularly assumed for mixtures in risk assessment, which however might not be sufficiently protective in case of synergistic effects. Especially the prediction of combination effects of substances which do not share a common adverse outcome (AO) might be problematic. In this study, the focus was on the endpoint liver triglyceride accumulation in vitro, an indicator of hepatic fatty acid changes. The hepatotoxic compounds difenoconazole, propiconazole and tebuconazole were chosen which cause hepatic fatty acid changes in vivo, whereas fludioxonil was chosen as a hepatotoxic substance not causing fatty acid changes. Triglyceride accumulation was analyzed for combinations of steatotic and non-steatotic pesticides in human HepaRG hepatocarcinoma cells. Investigations revealed a potentiation of triglyceride accumulation by mixtures of the steatotic compounds with the non-steatotic fludioxonil, as compared to the single compounds. Mathematical modeling of combination effects indicated more than additive effects for the tested combinations if the method by Chou was applied, and a decrease in EC 50 values of the steatotic compounds when applied in mixtures. Use of an adverse outcome pathway (AOP)-driven testing strategy for liver steatosis showed interactions of the test compounds with the nuclear receptors AHR, CAR and PXR, as well as a downregulation of ACOX2 . An ACOX2-dependent mechanism underlying the observed mixture effect could not be verified using a siRNA approach. By contrast, a toxicokinetic interaction was identified including an inhibition of the metabolic enzyme CYP3A4 by fludioxonil and a decreased metabolic conversion of the CYP3A4 substrate difenoconazole when used in mixture experiments. In conclusion, an interaction by a steatotic and a non-steatotic compound at the toxicokinetic level on the endpoint triglyceride accumulation in vitro was described.

Intestinal and hepatic effects of iron oxide nanoparticles - Linn Voss; Elisa Hoché; Valerie Stock; Linda Böhmert; Albert Braeuning; Andreas F. Thünemann; Holger Sieg (Archives of Toxicology, 2021)
Iron oxide nanoparticles gain increasing attention due to their broad industrial use. However, safety concerns exist since their effects on human cells are still under investigation. The presence of iron oxide nanoparticles in the food pigment E172 has been shown recently. Here, we studied four iron oxide nanoparticles, one food pigment E172 and the ionic control FeSO 4 regarding dissolution in biological media, uptake and transport, and cellular effects in vitro in human intestinal Caco-2 and HepaRG hepatocarcinoma cells. The iron oxide nanoparticles passed the gastrointestinal passage without dissolution and reached the intestine in the form of particles. Minor uptake was seen into Caco-2 cells but almost no transport to the basolateral site was detected for any of the tested particles. HepaRG cells showed higher particle uptake. Caco-2 cells showed no alterations in reactive oxygen species production, apoptosis, or mitochondrial membrane potential, whereas two particles induced apoptosis in HepaRG cells, and one altered mitochondrial membrane potential at non-cytotoxic concentrations. No correlation between physicochemical particle characteristics and cellular effects was observed, thus emphasizing the need for case-by-case assessment of iron oxide nanoparticles.

Transcriptomics analysis of hepatotoxicity induced by the pesticides imazalil, thiacloprid and clothianidin alone or in binary mixtures in a 28-day study in female Wistar rats - Jimmy Alarcan; Heike Sprenger; Julia Waizenegger; Dajana Lichtenstein; Claudia Luckert; Philip Marx-Stoelting; Alfonso Lampen; Albert Braeuning (Archives of Toxicology, 2021)
Co-occurrence of pesticide residues in food commodities raises a potential safety issue as their mixture effects on human health are largely unknown. In a previous study, we reported the toxicological effects (pathology and histopathology) of imazalil (IMZ), thiacloprid (THI), and clothianidin (CTD) alone and in binary mixtures in a 28-day oral gavage study in female Wistar rats. Five dose levels (up to 350 mg/kg body weight/day) ranging from a typical toxicological reference value to a clear effect dose were applied. In the present study, we undertook a transcriptomics analysis of rat livers by means of total RNA sequencing (RNA-Seq). Bioinformatic data analysis involving Ingenuity Pathway Analysis (IPA) was used to gain mechanistic information on hepatotoxicity-related pathways affected after treatment with the pesticides, alone and in mixtures. Our data show that 2986 genes were differentially regulated by CTD while IMZ and THI had effects on 194 and 225 genes, respectively. All three individual compounds shared a common subset of genes whose network is associated with xenobiotic metabolism and nuclear receptor activation. Similar networks were retrieved for the mixtures. Alterations in the expression of individual genes were in line with the assumption of dose addition. Our results bring new insight into the hepatotoxicity mechanisms of IMZ, THI, and CTD and their mixtures.

Transcriptional and post-transcriptional regulation of the pregnane X receptor: a rationale for interindividual variability in drug metabolism - Tomas Smutny; Lucie Hyrsova; Albert Braeuning; Magnus Ingelman-Sundberg; Petr Pavek (Archives of Toxicology, 2021)

Cross-species analysis of hepatic cytochrome P450 and transport protein expression - Helen Hammer; Felix Schmidt; Philip Marx-Stoelting; Oliver Pötz; Albert Braeuning (Archives of Toxicology, 2021)
Most drugs and xenobiotics are metabolized in the liver. Amongst others, different cytochrome P450 (CYP) enzymes catalyze the metabolic conversion of foreign compounds, and various transport proteins are engaged in the excretion of metabolites from the hepatocytes. Inter-species and inter-individual differences in the hepatic levels and activities of drug-metabolizing enzymes and transporters result from genetic as well as from environmental factors, and play a decisive role in determining the pharmacokinetic properties of a compound in a given test system. To allow for a meaningful comparison of results from metabolism studies, it is, therefore, of utmost importance to know about the specific metabolic properties of the test systems, especially about the levels of metabolic enzymes such as the CYPs. Using a targeted proteomics approach, we, therefore, compared the hepatic levels of important CYP enzymes and transporters in different experimental systems in vivo and in vitro, namely Wistar rats, C57/Bl6 mice, mice humanized for the two xeno-sensing receptors PXR (pregnane-X-receptor) and CAR (constitutive androstane receptor), mice with human hepatocyte-repopulated livers, human HepaRG hepatocarcinoma cells, primary human hepatocytes, and human liver biopsies. In addition, the effects of xenobiotic inducers of drug metabolism on CYP enzymes and transporters were analyzed in selected systems. This study for the first time presents a comprehensive overview of similarities and differences in important drug metabolism-related proteins among the different experimental models.

β-catenin signaling, the constitutive androstane receptor and their mutual interactions - Albert Braeuning; Petr Pavek (Archives of Toxicology, 2020)
Aberrant signaling through β-catenin is an important determinant of tumorigenesis in rodents as well as in humans. In mice, xenobiotic activators of the constitutive androstane receptor (CAR), a chemo-sensing nuclear receptor, promote liver tumor growth by means of a non-genotoxic mechanism and, under certain conditions, select for hepatocellular tumors which contain activated β-catenin. In normal hepatocytes, interactions of β-catenin and CAR have been demonstrated with respect to the induction of proliferation and drug metabolism-related gene expression. The molecular details of these interactions are still not well understood. Recently it has been hypothesized that CAR might activate β-catenin signaling, thus providing a possible explanation for some of the observed phenomena. Nonetheless, many aspects of the molecular interplay of the two regulators have still not been elucidated. This review briefly summarizes our current knowledge about the interplay of CAR and β-catenin. By taking into account data and observations obtained with different mouse models and employing different experimental approaches, it is shown that published data also contain substantial evidence that xenobiotic activators of CAR do not activate, or do even inhibit signaling through the β-catenin pathway. The review highlights new aspects of possible ways of interaction between the two signaling cascades and will help to stimulate scientific discussion about the crosstalk of β-catenin signaling and the nuclear receptor CAR.

Impact of iron oxide nanoparticles on xenobiotic metabolism in HepaRG cells - Linn Voss; Kiymet Yilmaz; Lea Burkard; Janja Vidmar; Valerie Stock; Ute Hoffmann; Oliver Pötz; Helen Sophie Hammer; Matthias Peiser; Albert Braeuning; Katrin Löschner; Linda Böhmert; et al. (Archives of Toxicology, 2020)

Hepatotoxic pyrrolizidine alkaloids induce DNA damage response in rat liver in a 28-day feeding study - Johanna Ebmeyer; Josef Daniel Rasinger; Jan G. Hengstler; Dirk Schaudien; Otto Creutzenberg; Alfonso Lampen; Albert Braeuning; Stefanie Hessel-Pras (Archives of Toxicology, 2020)
Pyrrolizidine alkaloids (PA) are secondary plant metabolites that occur as food and feed contaminants. Acute and subacute PA poisoning can lead to severe liver damage in humans and animals, comprising liver pain, hepatomegaly and the development of ascites due to occlusion of the hepatic sinusoids (veno-occlusive disease). Chronic exposure to low levels of PA can induce liver cirrhosis and liver cancer. However, it is not well understood which transcriptional changes are induced by PA and whether all hepatotoxic PA, regardless of their structure, induce similar responses. Therefore, a 28-day subacute rat feeding study was performed with six structurally different PA heliotrine, echimidine, lasiocarpine, senecionine, senkirkine, and platyphylline, administered at not acutely toxic doses from 0.1 to 3.3 mg/kg body weight. This dose range is relevant for humans, since consumption of contaminated tea may result in doses of ~ 8 µg/kg in adults and cases of PA ingestion by contaminated food was reported for infants with doses up to 3 mg/kg body weight. ALT and AST were not increased in all treatment groups. Whole-genome microarray analyses revealed pronounced effects on gene expression in the high-dose treatment groups resulting in a set of 36 commonly regulated genes. However, platyphylline, the only 1,2-saturated and, therefore, presumably non-hepatotoxic PA, did not induce significant expression changes. Biological functions identified to be affected by high-dose treatments (3.3 mg/kg body weight) comprise cell-cycle regulation associated with DNA damage response. These functions were found to be affected by all analyzed 1,2-unsaturated PA. In conclusion, 1,2-unsaturated hepatotoxic PA induced cell cycle regulation processes associated with DNA damage response. Similar effects were observed for all hepatotoxic PA. Effects were observed in a dose range inducing no histopathological alterations and no increase in liver enzymes. Therefore, transcriptomics studies identified changes in expression of genes known to be involved in response to genotoxic compounds at PA doses relevant to humans under worst case exposure scenarios.

Impairment of bile acid metabolism by perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) in human HepaRG hepatoma cells - Anne-Cathrin Behr; Anna Kwiatkowski; Marcus Ståhlman; Felix Florian Schmidt; Claudia Luckert; Albert Braeuning; Thorsten Buhrke (Archives of Toxicology, 2020)
Perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) are man-made chemicals that are used for the fabrication of many products with water- and dirt-repellent properties. The toxicological potential of both substances is currently under debate. In a recent Scientific Opinion, the European Food Safety Authority (EFSA) has identified increased serum total cholesterol levels in humans as one major critical effect being associated with exposure to PFOA or PFOS. In animal studies, both substances induced a decrease of serum cholesterol levels, and the underlying molecular mechanism(s) for these opposed effects are unclear so far. In the present study, we examined the impact of PFOA and PFOS on cholesterol homoeostasis in the human HepaRG cell line as a model for human hepatocytes. Cholesterol levels in HepaRG cells were not affected by PFOA or PFOS, but both substances strongly decreased synthesis of a number of bile acids. The expression of numerous genes whose products are involved in synthesis, metabolism and transport of cholesterol and bile acids was strongly affected by PFOA and PFOS at concentrations above 10 µM. Notably, both substances led to a strong decrease of CYP7A1, the key enzyme catalyzing the rate-limiting step in the synthesis of bile acids from cholesterol, both at the protein level and at the level of gene expression. Moreover, both substances led to a dilatation of bile canaliculi that are formed by differentiated HepaRG cells in vitro. Similar morphological changes are known to be induced by cholestatic agents in vivo. Thus, the strong impact of PFOA and PFOS on bile acid synthesis and bile canalicular morphology in our in vitro experiments may allow the notion that both substances have a cholestatic potential that is connected to the observed increased serum cholesterol levels in humans in epidemiological studies.

Array-based Western-blotting reveals spatial differences in hepatic signaling and metabolism following CAR activation - Fridolin Treindl; Elke Zabinsky; Simon Kling; Michael Schwarz; Albert Braeuning; Markus F. Templin (Archives of Toxicology, 2020)

Combinations of LXR and RXR agonists induce triglyceride accumulation in human HepaRG cells in a synergistic manner - Alexandra Lasch; Jimmy Alarcan; Alfonso Lampen; Albert Braeuning; Dajana Lichtenstein (Archives of Toxicology, 2020)

Inflammation-associated suppression of metabolic gene networks in acute and chronic liver disease - Gisela Campos; Wolfgang Schmidt-Heck; Jonathan De Smedt; Agata Widera; Ahmed Ghallab; Larissa Pütter; Daniela González; Karolina Edlund; Cristina Cadenas; Rosemarie Marchan; Reinhard Guthke; Catherine Verfaillie; et al. (Archives of Toxicology, 2020)

The pyrrolizidine alkaloid senecionine induces CYP-dependent destruction of sinusoidal endothelial cells and cholestasis in mice - Stefanie Hessel-Pras; Albert Braeuning; Georgia Guenther; Alshaimaa Adawy; Anne-Margarethe Enge; Johanna Ebmeyer; Colin J. Henderson; Jan G. Hengstler; Alfonso Lampen; Raymond Reif (Archives of Toxicology, 2020)

Uptake and effects of orally ingested polystyrene microplastic particles in vitro and in vivo - Valerie Stock; Linda Böhmert; Elisa Lisicki; Rafael Block; Julia Cara-Carmona; Laura Kim Pack; Regina Selb; Dajana Lichtenstein; Linn Voss; Colin J. Henderson; Elke Zabinsky; Holger Sieg; et al. (Archives of Toxicology, 2019)

Okadaic acid activates Wnt/β-catenin-signaling in human HepaRG cells - Jessica Dietrich; Cornelia Sommersdorf; Svenja Gohlke; Oliver Poetz; Bjoern Traenkle; Ulrich Rothbauer; Stefanie Hessel-Pras; Alfonso Lampen; Albert Braeuning (Archives of Toxicology, 2019)

Prediction of human drug-induced liver injury (DILI) in relation to oral doses and blood concentrations - Wiebke Albrecht; Franziska Kappenberg; Tim Brecklinghaus; Regina Stoeber; Rosemarie Marchan; Mian Zhang; Kristina Ebbert; Hendrik Kirschner; Marianna Grinberg; Marcel Leist; Wolfgang Moritz; Cristina Cadenas; et al. (Archives of Toxicology, 2019)

In vitro characterization of hepatic toxicity of Alternaria toxins - Stefanie Hessel-Pras; Janine Kieshauer; Giana Roenn; Claudia Luckert; Albert Braeuning; Alfonso Lampen (Mycotoxin Research, 2019)

Pregnane X receptor mediates steatotic effects of propiconazole and tebuconazole in human liver cell lines - Constanze Knebel; Thorsten Buhrke; Roderich Süssmuth; Alfonso Lampen; Philip Marx-Stoelting; Albert Braeuning (Archives of Toxicology, 2019)

In vitro proteomic analysis of methapyrilene toxicity in rat hepatocytes reveals effects on intermediary metabolism - Albert Braeuning; Axel Oberemm; Tanja Heise; Ursula Gundert-Remy; Jan G. Hengstler; Alfonso Lampen (Archives of Toxicology, 2019)

Plausibility of microplastic uptake in a paper by Deng et al., Scientific reports 7:46687, 2017 - Linda Böhmert; Valerie Stock; Albert Braeuning (Archives of Toxicology, 2019)

Uptake of microplastics and related health effects: a critical discussion of Deng et al., Scientific reports 7:46687, 2017 - Albert Braeuning (Archives of Toxicology, 2019)

Toxicogenomics directory of rat hepatotoxicants in vivo and in cultivated hepatocytes - Marianna Grinberg; Regina M. Stöber; Wiebke Albrecht; Karolina Edlund; Markus Schug; Patricio Godoy; Cristina Cadenas; Rosemarie Marchan; Alfonso Lampen; Albert Braeuning; Thorsten Buhrke; Marcel Leist; et al. (Archives of Toxicology, 2018)

Propiconazole is an activator of AHR and causes concentration additive effects with an established AHR ligand - Constanze Knebel; Juliane Kebben; Ivano Eberini; Luca Palazzolo; Helen S. Hammer; Roderich D. Süssmuth; Tanja Heise; Stefanie Hessel-Pras; Alfonso Lampen; Albert Braeuning; Philip Marx-Stoelting (Archives of Toxicology, 2018)

On the necessity of careful interpretation of omics data - Albert Braeuning; Falko Frenzel; Alfonso Lampen (Archives of Toxicology, 2018)

Nanomaterials: certain aspects of application, risk assessment and risk communication - Peter Laux; Jutta Tentschert; Christian Riebeling; Albert Braeuning; Otto Creutzenberg; Astrid Epp; Valérie Fessard; Karl-Heinz Haas; Andrea Haase; Kerstin Hund-Rinke; Norbert Jakubowski; Peter Kearns; et al. (Archives of Toxicology, 2018)

Oxidative inactivation of the endogenous antioxidant protein DJ-1 by the food contaminants 3-MCPD and 2-MCPD - Thorsten Buhrke; Linn Voss; Anja Briese; Heike Stephanowitz; Eberhard Krause; Albert Braeuning; Alfonso Lampen (Archives of Toxicology, 2018)

Adverse outcome pathways: opportunities, limitations and open questions - Marcel Leist; Ahmed Ghallab; Rabea Graepel; Rosemarie Marchan; Reham Hassan; Susanne Hougaard Bennekou; Alice Limonciel; Mathieu Vinken; Stefan Schildknecht; Tanja Waldmann; Erik Danen; Ben van Ravenzwaay; et al. (Archives of Toxicology, 2017)

A frequent misinterpretation in current research on liver fibrosis: the vessel in the center of CCl4-induced pseudolobules is a portal vein - Seddik Hammad; Albert Braeuning; Christoph Meyer; Fatma El Zahraa Ammar Mohamed; Jan G. Hengstler; Steven Dooley (Archives of Toxicology, 2017)

Lanthanum chloride precipitation-based toxicoproteomic analysis of 3-monochloropropane-1,2-diol toxicity in rat kidney reveals involvement of extracellular signal-regulated kinase 2 - Axel Oberemm; Monique Braun; Stefanie Sawada; Mario Pink; Falko Frenzel; Christel Rozycki; Christine Meckert; Elke Zabinsky; Albert Braeuning; Alfonso Lampen (Archives of Toxicology, 2017)

Comparative proteomic analysis of 2-MCPD- and 3-MCPD-induced heart toxicity in the rat - Katharina Schultrich; Falko Frenzel; Axel Oberemm; Thorsten Buhrke; Albert Braeuning; Alfonso Lampen (Archives of Toxicology, 2017)

Hepatotoxic effects of cyproconazole and prochloraz in wild-type and hCAR/hPXR mice - Philip Marx-Stoelting; Katrin Ganzenberg; Constanze Knebel; Flavia Schmidt; Svenja Rieke; Helen Hammer; Felix Schmidt; Oliver Pötz; Michael Schwarz; Albert Braeuning (Archives of Toxicology, 2017)

Wirkungsbezogene Analytik – Konzepte für die Fort- und Weiterentwicklung - Albert Braeuning; Alfonso Lampen (Journal of Consumer Protection and Food Safety, 2017)

Comparative analysis of 3D culture methods on human HepG2 cells - Claudia Luckert; Christina Schulz; Nadja Lehmann; Maria Thomas; Ute Hofmann; Seddik Hammad; Jan G. Hengstler; Albert Braeuning; Alfonso Lampen; Stefanie Hessel (Archives of Toxicology, 2017)

1. Treffen des wissenschaftlichen Netzwerkes zur Authentizitätsprüfung von Lebens- und Futtermitteln - Carsten Fauhl-Hassek; Susanne Esslinger; Janet Riedl; Anja Buschulte; Albert Braeuning; Stefan Weigel; Monika Lahrssen-Wiederholt; Reiner Wittkowski (Journal of Consumer Protection and Food Safety, 2016)

Is the question of phenobarbital as potential liver cancer risk factor for humans really resolved? - Albert Braeuning; Michael Schwarz (Archives of Toxicology, 2016)

Tumor promotion and inhibition by phenobarbital in livers of conditional Apc-deficient mice - Albert Braeuning; Alina Gavrilov; Miriam Geissler; Christine Wenz; Sabine Colnot; Markus F. Templin; Ute Metzger; Michael Römer; Andreas Zell; Michael Schwarz (Archives of Toxicology, 2016)

Proteomic analysis of 3-MCPD and 3-MCPD dipalmitate-induced toxicity in rat kidney - Stefanie Sawada; Axel Oberemm; Thorsten Buhrke; Julia Merschenz; Albert Braeuning; Alfonso Lampen (Archives of Toxicology, 2016)

Wirkungsbezogene Analytik: Neue Konzepte für die Überwachung und Lebensmittelsicherheit - Albert Braeuning; Hermann Broll; Alfonso Lampen (Journal of Consumer Protection and Food Safety, 2016)

Firefly luciferase inhibition: a widely neglected problem - Albert Braeuning (Archives of Toxicology, 2015)

Liver cell proliferation and tumor promotion by phenobarbital: relevance for humans? - Albert Braeuning (Archives of Toxicology, 2014)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Selective poisoning of Ctnnb1-mutated hepatoma cells in mouse liver tumors by a single application of acetaminophen - Yasmin Singh; Albert Braeuning; Andreas Schmid; Bernd J. Pichler; Michael Schwarz (Archives of Toxicology, 2013)

Non-melanoma skin cancer in mouse and man - Michael Schwarz; Peter A. Münzel; Albert Braeuning (Archives of Toxicology, 2013)

Mechanisms of RAS/β-catenin interactions - Eva Zeller; Katharina Hammer; Melissa Kirschnick; Albert Braeuning (Archives of Toxicology, 2013)

The connection of β-catenin and phenobarbital in murine hepatocarcinogenesis: a critical discussion of Awuah et al., PLoS ONE 7(6):e39771, 2012 - Albert Braeuning (Archives of Toxicology, 2013)

Paradoxical cytotoxicity of tert-butylhydroquinone in vitro: what kills the untreated cells? - Albert Braeuning; Silvia Vetter; Silvia Orsetti; Michael Schwarz (Archives of Toxicology, 2012)

Die Regulation des Fremdstoffmetabolismus durch β-Catenin - Albert Braeuning (BIOspektrum, 2012)

Phenotype of single hepatocytes expressing an activated version of β-catenin in liver of transgenic mice - Sandra Schreiber; Benjamin Rignall; Albert Braeuning; Philip Marx-Stoelting; Thomas Ott; Albrecht Buchmann; Seddik Hammad; Jan G. Hengstler; Michael Schwarz; Christoph Köhle (Journal of Molecular Histology, 2011)

Phenotype and growth behavior of residual β-catenin-positive hepatocytes in livers of β-catenin-deficient mice - Albert Braeuning; Yasmin Singh; Benjamin Rignall; Albrecht Buchmann; Seddik Hammad; Amnah Othman; Iris Recklinghausen; Patricio Godoy; Stefan Hoehme; Dirk Drasdo; Jan G. Hengstler; Michael Schwarz (Histochemistry and Cell Biology, 2010)